The Analysis of the Issuance Quality of the Driving License (SIM) at the Police Office of Gorontalo Regency - Satria Hadita; Titin Dunggio; Irwan Halid (LP2M Universitas Bina Mandiri Gorontalo, 2021)
The Analysis of the Issuance Quality of the Driving License (SIM) at the Police Office of Gorontalo Regency. The objectives of this study are: 1) to determine the quality of administrative service provision for a driving license at the police office of Gorontalo Regency; 2) to know the determining factors in the police office of Gorontalo Regency in improving the quality of public services; 3) to know the efforts made by the Gorontalo Police Traffic Unit in overcoming the problem of improving the quality of public services. This study uses a qualitative approach with in-depth interviews with informants, namely direct and service staff on the object under study. Data sources, namely: primary data, namely data obtained directly from the object of research and processed by the researcher himself, secondary data, namely data related to previous research data and from institutions related to the variables studied. The results of this study indicate that the Satpas of the Gorontalo Police Traffic Unit has not fulfilled adequate service facilities in providing quality public services to the community such as: facilities and infrastructure as well as human resources. However, the officers have shown an attitude of responsiveness to help the community when they experience difficulties during the process of making a driving license administration.